CONTRACT LAW AND THE LIVING ENVIRONMENT: CONTRACTUAL LIABILITY IN SUSTAINABLE DEVELOPMENT - Dwitanto, Hendri; Natsir, Muhammad; Nasution, Fahman Urdawi (NOMOI Law Review, 2025)
Sustainable development in coastal areas requires effective legal instruments to ensure environmental responsibility in every development activity. This research analyzes the role of contract law as an enforcement instrument of contractual responsibility in the sustainable development in Indonesia's coastal areas. The purpose of this study is to examine the legal foundation of contractual responsibility in coastal development contracts, analyze the implementation of environmental clauses in development contracts, and formulate an ideal legal framework to strengthen contractual responsibility in sustainable development. The research method uses a normative juridical approach with an analysis of legislation, academic journals, and related legal literature. The results indicate that the legal basis for contractual liability is provided through Law Number 32 of 2009 concerning Environmental Protection and Management and Law Number 1 of 2014 on Amendments to Law Number 27 of 2007 on Coastal and Small Islands Management. However, its implementation is still hindered by weak oversight mechanisms and law enforcement. The conclusion of the research suggests that contract law plays a strategic role in achieving sustainable development through environmental clauses that legally bind the parties, but there is a need for strengthening institutions and oversight mechanisms to ensure effective implementation in the society.